The Principles and Practice of Selling / Published on Behalf of the Chartered Institute of Marketing - Gillam Alan (Butterworth Heinemann, 1990)
The Book examines the attributes sales people require and shows how they can develop themselves to improve their performance. Preface, The Salesman, The Product, Planning a Sales Journey and Prospection, The Sales Interview, Psychological Consideration of Moods and Motives, Overcoming Objections and Handling Complaints, Sales Reporting and Records, Variations in Selling Situations, Selling to Industry, Career Prospects, Bibliography, Index.